Differentiation Between Benign and Malignant Pigmented Skin Tumours Using Bedside Diagnostic Imaging Technologies: A Pilot Study - Terese von Knorring; Niels Møller Israelsen; Vilde Ung; Julie L. Formann; Mikkel Jensen; Merete Hædersdal; Ole Bang; Gabriella Fredman; Mette Mogensen (Medical Journals Sweden, 2022)
Rapid diagnosis of suspicious pigmented skin lesions is imperative; however, current bedside skin imaging technologies are either limited in penetration depth or resolution. Combining imaging methods is therefore highly relevant for skin cancer diagnostics. This pilot study evaluated the ability of optical coherence tomography, reflectance confocal microscopy, photo-acoustic imaging and high-frequency ultrasound to differentiate malignant from benign pigmented skin lesions. A total of 41 pigmented skin tumours were scanned prior to excision. Morphological features and blood vessel characteristics were analysed with reflectance confocal microscopy, optical coherence tomography, high-frequency ultrasound and photoacoustic imaging images, and the diagnostic accuracy was assessed. Three novel photoacoustic imaging features, 7 reflectance confocal microscopy features, and 2 optical coherence tomography features were detected that had a high correlation with malignancy; diagnostic accuracy > 71%. No significant features were found in high-frequency ultrasound. In conclusion, optical coherence tomography, reflectance confocal microscopy and photoacoustic imaging in combination enable image-guided bedside evaluation of suspicious pigmented skin tumours. Combining these advanced techniques may enable more efficient diagnosis of skin cancer.